Simulated Live Transportation of Fishes in Tanks Under Light and Dark Conditions - M.R., Raghunath; prasanth, Hema; N., Sridhar; C.P., Chitra (Fishery Technology, 2025)
Live fish command higher price in the fresh fish market than dead iced fish. Preliminary trials were held to find the effect of light and dark conditions on live fish transportation for the fresh fish market. Sub-adult Rohu (Labeo rohita) of 220-250g were held at high density (130 fish.m"3) in aquarium and plastic tank to simulate live fish transportation conditions. The effect of light and dark conditions on oxygen consumption, ammonia build-up, pH and temperature were monitored during the study. Average rates of decrease in dissolved oxygen (DO) were highest under full light conditions (3.2ppm DO.h"1) followed by semi dark and least in fully dark conditions (1.94 ppm DO.h"1). Similar results were seen when fish were held in plastic tanks as well. Increased levels of salinity in water decreased the DO depletion rates (1.5-1.98 ppm DO.h"1). Ammonia concentrations increased rapidly under fully dark conditions in presence of 0.9 and 1.1% salt (0.8-1.59 ppm NHj.h"1). Lowest rates of increase in ammonia concentrations were seen under full light conditions (0.68 ppm NHj.h"1). The pH under all conditions of holding decreased steadily in spite of the increase in ammonia. It is concluded that dark conditions are beneficial for live fish transportation provided the fecal matter could be removed effectively to counter the build-up of ammonia.